Analisis Risiko Bunuh Diri pada Mahasiswa Kesehatan di Kota Banda Aceh - Sri Novitayani; Irfanita Nurhidayah (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Suicide is the main cause of death for students. Some studies report that half of college students have felt so depressed that they were useful. College life can be a time of high stress. This study aims to describe the risk of suicide in health students in Banda Aceh.Methods: This type of research is a quantitative research using a descriptive correlative method. The sampling technique in this study used purposive sampling with a sample of 171 students. Data collection method using Adult Suicidal Ideation Questionnaire (ASIQ).Result: The majority of respondents were health students from the Faculty of Nursing (67.3%), female (88.9%), 2016 class (50.9%), adult (90.6%), from high school (84 ,8%), both parents are still alive (85.4%), have parents who work as civil servants (52.6%), and live in a boarding house/rent (50.3%). The age of the students in this study was between 18 years to 23 years. The majority of health students at Syiah Kuala University experienced a low risk of suicide (87.7%).Conclusion : It can be concluded that health students have a suicide risk which is characterized by thoughts related to suicidal ideation, but these ideas rarely appear so that their suicide risk category is low.